2014
DOI: 10.26719/2014.20.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary habits and body mass index of adolescent females in intermediate schools in Riyadh, Saudi Arabia

Abstract: Obesity among Saudi youth is a growing public health challenge. This cross-sectional study measured body mass index (BMI) and determined the eating habits and lifestyle of 107 randomly selected female adolescent students (age 12-15 years) at schools in Riyadh. The students' heights and weights were measured and a pre-tested questionnaire was used to collect data on diet and lifestyle. The majority of the students' families had monthly income > 10 000 riyals (US$ 1 = 3.75 riyals). About half the students (53.3%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 16 publications
9
22
1
Order By: Relevance
“…The age of university students is higher than the age of the adolescent students in the other studies, and willingness of nursing students to keep their weight within normal range. These results going in line with the similar studies; [33] and [8], represented that, about half the students were within normal weight, while more than one fourth of them were underweight. As well, [34], explored that the great bulk of the students were of normal weight; more than one-fourth were underweight; and few percentage of them were overweight/obese students.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The age of university students is higher than the age of the adolescent students in the other studies, and willingness of nursing students to keep their weight within normal range. These results going in line with the similar studies; [33] and [8], represented that, about half the students were within normal weight, while more than one fourth of them were underweight. As well, [34], explored that the great bulk of the students were of normal weight; more than one-fourth were underweight; and few percentage of them were overweight/obese students.…”
Section: Discussionsupporting
confidence: 80%
“…Also, According to the results of [53] and [47], all of the university students ate daily snakes. As well, [48] and [8], indicated that the majority of adolescent students consumed snakes between breakfast and lunch as well as between lunch and dinner. This in line with [45] and [25] ,who reported greater levels of dietary devotion among the university students for snakes.…”
Section: Unhealthy Eating Habitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many respondents reported eating junk food regularly while few admitted that they consumed fruit and milk. This has severe implications for oral health, systemic health and intellectual development (10,25). School management should regulate the types of foods being sold in the cafeteria and the types of lunch and snacks being brought from home.…”
Section: Discussionmentioning
confidence: 99%
“…The study conducted by Al-Muammar et al assessing the relationship between food behavior and BMI in adolescent high school girls in Saudi Arabia also showed no significant relationships (23). These findings, however, might be caused by measurement errors of height and weight, nonaccurate reports of food frequency, or the small size of the sample.…”
Section: Discussionmentioning
confidence: 89%